Hybrid optogenetic and electrical stimulation for greater spatial resolution and temporal fidelity of cochlear activation. (28th October 2020) - Thompson, Alex C; Wise, Andrew K; Hart, William L; Needham, Karina; Fallon, James B; Gunewardene, Niliksha; Stoddart, Paul R; Richardson, Rachael T
Abstract: Objective. Compared to electrical stimulation, optogenetic stimulation has the potential to improve the spatial precision of neural activation in neuroprostheses, but it requires intense light and has relatively poor temporal kinetics. We tested the effect of hybrid stimulation, which is the combination of subthreshold optical and electrical stimuli, on spectral and temporal fidelity in the cochlea by recording multiunit activity in the inferior colliculus of channelrhodopsin (H134R variant) transgenic mice. Approach. Pulsed light or biphasic electrical pulses were delivered to cochlear spiral ganglion neurons of acutely deafened mice, either as individual stimuli or as hybrid stimuli for which the timing of the electrical pulse had a varied delay relative to the start of the optical pulse. Response thresholds, spread of activation and entrainment data were obtained from multi-unit recordings from the auditory midbrain. Main results. Facilitation occurred when subthreshold electrical stimuli were applied at the end of, or up to 3.75 ms after subthreshold optical pulses. The spread of activation resulting from hybrid stimulation was significantly narrower than electrical-only and optical-only stimulation (p < 0.01), measured at equivalent suprathreshold levels of loudness that are relevant to cochlear implant users. Furthermore, temporal fidelity, measured as maximum following rates to 300 ms pulse trains bursts up to 240 Hz, was 2.4-fold greater than optical-only stimulation (p < 0.05). Significance. By significantly improving spectral resolution of electrical- and optical-only stimulation and the temporal fidelity of optical-only stimulation, hybrid stimulation has the potential to increase the number of perceptually independent stimulating channels in a cochlear implant.